2022
DOI: 10.3390/app13010474
|View full text |Cite
|
Sign up to set email alerts
|

The Power Setting of Focused Ultrasound for the Palliative Treatment of Advanced Pancreatic Cancer: A Study in an Ex Vivo Bovine Liver

Abstract: High-intensity focused ultrasound (HIFU) ablation has been widely used in advanced pancreatic cancer in recent years. In numerous studies, HIFU has been shown to be safe, effective, and practicable, but there are a few HIFU-related adverse effects. The patients’ discomfort during therapy increased proportionally with increasing delivered energy and pain levels seemed to be independent of the dose of anesthetic or sedation. If the power used in therapy is too high, the temperature of the target area will rise r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…VHA occur at the thermocouple tissue interface, caused by the difference in the densities between the thermocouple and the surrounding tissue [21]. In 2008,Morris et al showed temperature measurements using metal wire thermocouples can have an error of up to 80% [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VHA occur at the thermocouple tissue interface, caused by the difference in the densities between the thermocouple and the surrounding tissue [21]. In 2008,Morris et al showed temperature measurements using metal wire thermocouples can have an error of up to 80% [22].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, waiting times such as 0.5 s after the start of ultrasound or 200 milliseconds [23], 2 s [24], and 5 s [25] after ultrasound cessation have been reported. Another method is simulation, used to estimate the temperature increase caused by viscous heating and correct the temperature reading [22]. No matter which method is used, there are inconveniences, which also highlight the limitations of thermocouples.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers generally aim to prevent and mitigate the impact of cavitation effects during the design phase. On the other hand, the cavitation phenomenon plays a crucial role in ultrasound-based therapeutic diagnosis [4,5], which requires prior cavitation prediction. Thus, to both prevent and leverage the cavitation effect, estimating its intensity in the target flow field is vital.…”
Section: Introductionmentioning
confidence: 99%